Association between constipation and the urine albumin-to-creatinine ratio in adults: the NHANES 2009–2010 - Yang, Yuying; Rao, Siyi; Zhuo, Yongjie; Fang, Yuan; Wan, Jianxin; You, Danyu (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to analyze the association between constipation and the urine albumin-to-creatinine ratio (ACR) using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2010.MethodsIn this cross-sectional study, a sample of 4,282 adults aged 20 and older was selected from the NHANES 2009–2010. Constipation was defined as having fewer than three bowel movements per week. The average of the two ACR measurements was used as the outcome variable. Logistic regression models (non-adjusted and multivariate adjusted models) were used to examine the relationship between constipation and ACR. Subgroup and interaction analyses related to gender, age, smoking, alcohol consumption, body mass index (BMI), hypertension, and diabetes were also conducted to assess the stability of the association between constipation and ACR.ResultsIn this study population of 4,282 individuals, 352 individuals with an ACR of 30 mg/g or higher were considered to have albuminuria. The prevalence of constipation was higher in the albuminuria group compared to the non-albuminuric group (6.4% vs. 3.5%, p = 0.002). The unadjusted model (Model I) showed an increased risk of ACR associated with constipation (OR 1.81, 95% CI 1.13–2.91, p = 0.014). After controlling for gender, age, race/ethnicity, marital status, and education level in Model II, the association between constipation and ACR remained significant (OR 2.20, 95% CI 1.34–3.60, p = 0.002). Upon further adjustment for BMI, smoking status, alcohol consumption, diabetes, hypertension, arthritis, asthma, coronary heart disease, liver disease, cancer, blood urea nitrogen (BUN), serum creatinine (Scr), uric acid (UA) and estimated glomerular filtration rate (eGFR) in Model III, the positive association between constipation and ACR was still significant (OR 1.88, 95% CI 1.09–3.23, p = 0.023). Subgroup analyses, stratified by gender, age, smoking status, alcohol consumption, BMI, hypertension, and diabetes, showed no statistically significant interactions (p > 0.05).ConclusionIn summary, this study found a positive association between constipation and urinary albumin excretion rate. The significant association between constipation and ACR highlights the need for clinicians to monitor urinary albumin levels in patients with constipation.